Aplikace scoring-modelu pro hodnocení nových dodavatelů - Chytilová, Ekaterina; Jurová, Marie (Univerzita Pardubice, 2012)
Nowadays increasing attention is paid to flexibility, elasticity of the supply chain. An essential part of building a solid but flexible supply chain is establishing and maintaining close cooperation with the supplier in the first stage. The position of customers in the relationship is affected by competition in the supply market, often taking the size and consistency of strategic of enterprises goals. Therefore, this article the authors pay attention to the evaluation of new (potential) suppliers in the first stage. The research is intended primarily for small and medium-sized enterprises making to order. The aim of this article is a sample application of MCE (The method of complex evaluation, scoring model) for the election of a new supplier in the first stage. Presentation of MCE application will be presented as single illustrative case study. In the article “The universal evaluation of new suppliers for small and medium sized companies” from authors Sutormina, E., Jurova, M. can be found the theoretical description of this methodology. The data presented in the article are real. The company wished to remain anonymous. MCE is oriented to properties of mediumsized enterprises.
The application of scoring-model for new supplier's evaluation
Keywords: supplier selection; new supplier evaluation; scoring model; supplier in the first stage